Model apatite systems for the stabilization of toxic metals : I, calcium lead vanadate - Dong, Zhili (2013)
Apatites of composition (Ca10−xPbx)(VO4)6F2 with 0 ≤x≤ 9 were synthesized by sintering in air at 800°C the oxides of calcium, lead, and vanadium that were mixed with calcium fluoride. Variations in lattice parameters, grain size, and durability were monitored as a function of composition. The expected dilation in unit cell edges with increasing replacement of calcium (IR = 1.26 Å) by lead (IR = 1.45 Å) was observed. The a cell edge (in angstroms) varied linearly (0.0458 x+ 9.7068) with x, while c followed the binomial function 0.0018x2+ 0.0279x+ 7.0118. Average grain sizes increased from approximately 5 μm (x= 0) to 25 μm (x= 9) as grain growth was enhanced due to incipient melting of the lead-rich compositions. For x < 5 the materials were biphasic. Overall dissolution, as determined by the toxicity characteristic leaching procedure (TCLP), was faster in calcium-rich apatites. Etching of well-crystallized apatite grains occurred preferentially on {1010} faces. These leach losses were augmented through the more rapid removal of cryptocrystalline regions and intergranular thin films.